2011
DOI: 10.3324/haematol.2011.057513
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combining dasatinib and FLAG-IDA for patients with chronic myeloid leukemia in blastic transformation

Abstract: using the HbA2 value of 3.4% as cut off. 8 Using the value of 30 mg/L for serum ferritin as cut off, 861 samples showed iron deficiency (ID) (group A) and 271 were without ID (group B) (Figure 1). The mean HbA2 value was 2.8%±0.79 in group A and 3.50%±1.23 in group B, with a significant difference (P=0.00001) among between the two groups. The distribution of the 253 samples with molecular analysis between groups A and B showed that 170 samples were part of group A and 83 of group B (Figure 1). From 170 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…In small series, this approach was shown to be highly efficacious, with unprecedented CR rates and a high probability of achieving CGR and major MRs. In accordance with expectations, the quality of MRs and length of survival were both higher in imatinib‐naïve patients . However, all cases of “cure” were observed after allogeneic HCT.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In small series, this approach was shown to be highly efficacious, with unprecedented CR rates and a high probability of achieving CGR and major MRs. In accordance with expectations, the quality of MRs and length of survival were both higher in imatinib‐naïve patients . However, all cases of “cure” were observed after allogeneic HCT.…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with expectations, the quality of MRs and length of survival were both higher in imatinibnaïve patients. 17,18 However, all cases of "cure" were observed after allogeneic HCT. Recently, investigators from the MD Anderson Cancer Center published their experience in treating patients with CML LBCs with combined intensive hyper-CVAD therapy and imatinib or dasatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Patients returning to a second CP (CP2) before allo-SCT have improved transplantation outcomes [97,98]. The addition of a TKI to chemotherapy-based AML [99,100] or ALL regimens [101] improves the chance of achieving CP2. The choice of TKI should be based on prior therapies and BCR-ABL1 KD-mutational status.…”
Section: Prevention By Elimination Of Bcr-abl1mentioning
confidence: 99%
“…Median BCR-ABL1/ABL1 ratio after the induction course was 0Á1%. Optimal results were also reported in elderly patients, with a 90% CR rate (Milojkovic et al, 2012). The authors reported four cases of BC treated with dasatinib (100 mg) plus FLAG/IDA (fludarabine, cytarabine, granulocyte colony-stimulating factor/idarubicin) regimen: one patient had lymphoid BC and achieved MMR after the first cycle of therapy, underwent HSCT and restarted dasatinib after transplant.…”
mentioning
confidence: 99%